Effect of the application of seaweed waste as fertilizers on growth and yield performance of brinjal (Solanum melongena L.) - Sivagini, K.; Sivashanthini, K.; Jeyavanan, K.; Sutharsiny, S.; Velauthamurthy, K. (Central Environmental Authority, Sri Lanka, 2019)
Seaweed is a macroalgal community that is commonly found in the coastal belt of Sri Lanka and is Underutilized. The use of seaweed as a fertilizer for crops is limited in the country. Therefore, this study was aimed to analyse the nutrient compositions of seaweeds and to assess the effects of seaweeds fertilizer application on the growth and yield of brinjal. Seaweeds such as Sargassum spp. and Turbinaria spp. were collected from the coastal regions of the Jaffna peninsula. The collected samples were dried and ground to a fine powder. Potting mixture for the crops was prepared by using different ratios of dried soil, cow dung, and seaweeds. Seven treatments were designed with three replicates such as soil as control (T1), soil + 100g Sargassum sp (T2), soil + 50g Sargassum spp+ 50g cow dung (T3), soil + 100g Tubineriya spp. (T4), soil + 50g Tubineriya spp. + 50g cow dung (T5), soil + cow dung at 2:1 ratio (T6) and soil + 100g cow dung (T7). Nutrients were analysed for both dried seaweed powder and potting mixture by using standard methods. Growth and yield of brinjal were observed and recorded. In Turbinaria spp. the estimated K, Na, N, Ca and P concentrations (ppt) were 3650±5.17, 837±1.76, 276±3.06, 163±4.18 and 19±1.53, respectively whereas in Sargassum spp. these were 2350±7.64, 794±2.19, 187±1.53, 221±1.33, and 17±1.53, respectively. Similarly, the pH of the seaweeds powder was slightly alkaline (pH=8±0.1). The amount of K in the potting mixture was dramatically decreased at the end of the experiment while amounts of N, P and Ca were constant. Plant height was significantly (p<0.05) differed at 2 weeks interval and at 14 th week, it was high (54.6±3.17 cm, p<0.05) in T6 followed by T7 (51.97± 0.83 cm). The total number of flowers was significantly (p=0.0001) high (40±0.34), in T6 next to T3 (36±0.33). The treatment T6 had a significant average fruit weight per plant (2,389±0.56g), next to T3 (2142±0.33 g). An average yield of brinjal was high (>39 tons/ha) in medium added with Sargassum spp. which was higher than (30 tons/ha) the recommended yield. A high amount of cow dung was added (2 kg) for T6 and only 50g was added for T3. However, both treatments T6 and T3 showed a better performance of growth and yield. Therefore, considering the cost of cow dung, it is recommended to use 50g Sargassum spp.+ 50 cow dung mixed with soil (T3) as a seaweed fertilizer for the brinjal cultivation.